Humans significantly metabolize and excrete the mycotoxin deoxynivalenol and its modified form deoxynivalenol-3-glucoside within 24 hours - Vidal, Arnau (Sci Rep, 2018)
For the first time, a comprehensive human intervention study was conducted to unravel the urinary excretion profile and metabolism of the fungal metabolite deoxynivalenol (DON) and its modified form deoxynivalenol-3-glucoside (DON-3-glucoside). Twenty volunteers were restricted in consuming cereals and cereal-based foods for 4 days. At day 3, a single bolus of 1 µg/kg body weight of DON and a single bolus of 1 µg/kg body weight of DON-3-glucoside after a washing-out period of two months was administered, and a 24-h urine collection was performed. The urine was analysed for DON, DON-3-glucoside, 3-ADON, 15-ADON, deepoxy-deoxynivalenol (DOM-1), deoxynivalenol-3-glucuronide (DON-3-glucuronide) and deoxynivalenol-15-glucuronide (DON-15-glucuronide). The urinary biomarker-analysis revealed that DON and DON-3-glucoside were rapidly absorbed, distributed, metabolized and excreted. Sixty-four % of the administered DON and 58% of DON-3-glucoside was recovered in the urine collected within 24 h. DON-15-glucuronide was the most prominent urinary biomarker followed by free DON and DON-3-glucuronide. Moreover, correlations among the presence of DON-15-glucuronide and DON-3-glucuronide were observed (within 24 hours (r = 0.61)). The DOM-1 detected in the urine was higher after the DON-3-glucoside administration. The obtained results are imperative to construct a standardized method to estimate DON-intake by means of urinary biomarkers.